Music‐based interventions for people living with dementia, targeting behavioral and psychological symptoms: A scoping review. (7th June 2021) - Sousa, Lídia; Neves, Maria J.; Moura, Bárbara; Schneider, Justine; Fernandes, Lia
Abstract: Introduction: Dementia care is a major public health issue worldwide. The management of behavioral and psychological symptoms (BPSD) is one of the hardest challenges in this context. Non‐pharmacological strategies, like music‐based interventions (Mbi), seem promising options, being considered low‐risk, widely available and inclusive. This scoping review aimed at mapping all Mbi used in dementia care, targeting BPSD, and debriefing its components, structure and rationale. Music therapy and other therapeutic music activities were included. Methods: The Arksey and O'Malley framework, Cochrane recommendations and PRISMA checklist were followed. Embase, PubMed, PsycINFO, ASSIA and Humanities Index were searched from first records until the 31 st of March 2020. Snowballing process and screening of relevant journals were also undertaken. A panel of experts critically guided the evidence synthesis. Results: Overall, 103 studies (34 RCT; 12 NRT; 40 Before/After studies and 17 Case Studies) met inclusion criteria. Basic elements of the Mbi, the rationale supporting its development and hypothesis tested were mostly underreported, thus hampering cross‐study comparisons and generalizations. Despite this, available evidence indicates that: it is feasible to deliver Mbi to PwD at very different stages and in different settings ‐ from community to the acute setting ‐ even for non‐music therapists; positive or neutral effects in BPSD are often reported but not without exception; individualization seems a critical factor mediating Mbi effects. Conclusions: Detailed intervention and research reporting are essential to interpretation, replication and translation into practice. Ten years after the publication of specific reporting guidelines, this goal is not yet fully achieved in music in dementia care. Key Points: This scoping review included studies reporting the administration of Music‐based Interventions (Mbi) to patients with dementia, targeting behavioral and psychological symptoms, independently of the setting. 103 studies (34 RCT; 12 NRT; 40 Before/After studies and 17 case Studies) were included in the analysis. There was a focus on mapping and detailing the intervention theory, content, delivery schedule and mode, interventionists, setting and treatment fidelity strategies. We identified more areas of doubt that remain to be elucidated than assumptions that can be directly translated to practice. Despite that, it was possible to infer some generalizations with clinical relevance.